THE FACTORS DRIVING SUCCESS IN SOUTH KOREAN EXPORTS: A CASE STUDY OF SAMSUNG ELECTRONINCS - Nurwulan Rizkiya Anjani; Tulus Warsito (Universitas Pendidikan Nasional, 2023)
South Korea is one of the prosperous countries because it rose from its economic crisis in the 1990s. This ginseng country has made many efforts to maintain stability and economic development by using diplomacy in international relations. South Korea carries out diplomatic activities to communicate with other countries, one of which is economic diplomacy. South Korea's diplomacy is their tool to promote exchanges that increase trade, culture, wealth and knowledge. One is expanding and improving their exports through multinational companies such as Samsung Electronics. This study identifies the elements contributing to South Korea's export success. Currently, South Korea is an example of a country in the East Asia Region those economy can increase yearly. This study uses qualitative research methods with literature studies to collect and analyze data or research objects written from the international relations perspective. The theory used in this study is the Porter-Diamond model and the concept of Export Oriented Development. The results of this study indicate that Samsung's global market dynamics have positively influenced South Korea's export success through Samsung's technological prowess, marketing approach, supply chain management, then political and international economic factors, as well as South Korea's economic diplomacy, which built and all are interconnected and strengthened.